Conflicts and configurations in a liminal space: SoTL scholars’ identity development (Teaching and Learning Inquiry, 2013)
Although academic identity has received attention in the literature, there have been few attempts to understand the influence on identity from engagement with the Scholarship of Teaching and Learning (SoTL). In this aper, we (a group of eight scholars from five different countries) describe how our interactions with SoTL have impacted the shaping of our academic identities. We have struggled to define the value, purpose, outcomes, and meanings of being a disciplined SoTL scholar, sometimes in addition to and sometimes in opposition to being a disciplinary scholar. Through analysis of our own 100-word reflective narratives, we identify common conflicts and configurations around our experiences of developing a SoTL identity. We describe how navigating among conflicting identities can lead us into a troublesome but deeply reflective liminal space, prompting profound realizations and the reconstruction of academic identity. Drawing on this notion of liminality helps us to understand our journeys as moving through a necessary and important transformational landscape, and allows us to suggest ways to support those engaging with SoTL to develop an integrative SoTL identity.